Strategi Penggunaan Youtube Sebagai Sarana Menyebarluaskan Berita (Studi Di Harian Umum Palembang Ekspres) - Hadimas Pratama; Candra Darmawan; Muslimin (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This thesis is entitled Strategies for Using YouTube as a Means of Disseminating News (Study in the Public Daily Palembang Express). The aim of this research is to find out the strategies for using YouTube as a means of disseminating news by the Palembang Express General Daily and to find out what are the supporting and inhibiting factors for the Palembang Express General Daily in disseminating news via YouTube. This study used descriptive qualitative method. The types of data used are primary and secondary. Data collection tools are observation, interviews and documentation. The informants were 2 Palembang Ekspres staff. In this research, Miles Huberman's interactive analysis is: data reduction, data description, data presentation, and conclusions. The results of this research show that the strategy used by the Palembang Express Public Daily to disseminate news via YouTube is to create attractive titles and thumbnails, choosing interesting titles and thumbnails that can influence the audience, creating a special team to coordinate and create content on YouTube, increasing the number of programs with There are many programs, so viewers can choose what programs they like on YouTube Palembang Ekspres. And the last thing is to regularly post videos so that you can meet the information needs of the audience. The supporting factors for the Palembang Express General Daily in disseminating news via YouTube are adequate equipment to create good and quality video content. Apart from that, the audience's response also has an influence as a supporting factor because criticism, suggestions and appreciation become evaluation material so that YouTube Palembang Ekspres content can be even better. Another supporting factor is team commitment, hard work and team discipline which is very influential in disseminating news via YouTube. Apart from that, there are also inhibiting factors, namely obstacles in attracting audience interest due to changing audience tastes and slow internet networks which slightly hinder the dissemination of news via YouTube.